Current standards for diagnosis of syphilis: comparing the russian and foreign guidelines (part I) - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Despite the abundance of existing laboratory methods the diagnosis of syphilis still faces many challenges. Though direct detection of T. pallidum plays an important role in early manifest forms of the disease, serological tests remain the mainstay of diagnosis. Traditional syphilis screening algorithm based on nontreponemal tests with subsequent confirmation using treponemal tests is a standard worldwide. Recently, the ability to automate the treponemal tests promotes the increasingly widespread implementation of reverse algorithm when these tests are used for syphilis screening. None of the current serological algorithms are able to reliably differentiate between active and previously treated syphilis, which causes uncertainty in the management of patients. There is no «gold standard» for the diagnosis of neurosyphilis, ocular, auricular and visceral syphilis. The interpretation of serological tests in children born to seropositive mothers is also complicated. Diagnosis of congenital syphilis in newborns and, consequently, the prescription of antibiotic therapy often depends on assessment of the adequacy of maternal treatment during pregnancy, which leads to subjective decisions. This article provides a comparative analysis of the «Federal guidelines for the management of patients with syphilis» and their foreign analogues, discusses significant peculiarities of these guidelines and reviews current concerns and controversies in syphilis diagnosis.